Сейсмічна добротність земної кори північної частини Українського щита - Андрущенко, Ю.А.; Осадчий, В.І.; Лящук, О.І.; Грабченко, В.В. (Геофизический журнал, 2016)
По записям поверхностных кода-волн от сейсмических событий в районе г. Кривой Рог получены значения добротности (Q), частотного параметра (n) и коэффициента затухания (δ) сейсмических волн в земной коре северной части Украинского щита. Для определения добротности использованы цифровые записи сейсмических сигналов из района Кривого Рога, полученные сетью сейсмических наблюдений Главного центра специального контроля (ГЦСК) в течение последних 10 лет. Эмпирическая зависимость Qc(f) для северной части Украинского щита использована при уточнении формулы расчета магнитуды по поверхностной Lg-волне, являющейся основой надежных магнитудных оценок региональных сейсмических событий. Сделан вывод о современном уровне тектонической активности в исследуемом регионе. According to the records of superficial coda-waves from seismic events in the Kriviy Rig area receive value, quality factor (Q), frequency parameter (n) and attenuation factor (δ) of seismic waves in earth's crust of northern part Ukrainian shield have been obtained. To determine the quality factor digital recording of seismic signals from the area of Kriviy Rig produced network of seismic observations of the Main center of the special control (MCSK) over the last 10 years were used. The resulting empirical relationship for the northern part of the Ukrainian shield Qc(f) was used to clarify the formula for calculating the magnitude of the surface on the Lg-wave. Based on these data, the conclusion on the present level of tectonic activity in the study area has been made.